2009
DOI: 10.1016/j.neulet.2008.10.054
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic changes in cortical NADH fluorescence in rat focal ischemia: Evaluation of the effects of hypothermia on propagation of peri-infarct depolarization by temporal and spatial analysis

Abstract: Suppression of peri-infarct depolarizations (PIDs) is one of the major mechanisms of hypothermic protection against transient focal cerebral ischemia. Previous studies have shown the lack of hypothermic protection against permanent focal ischemia. We hypothesized the lack of hypothermic protection was due to the poor efficacy in suppression of PIDs. To examine the hypothesis, we elucidated the effects of hypothermia on the manner of propagation of PIDs with temporal and spatial resolutions using NADH (reduced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 17 publications
2
10
0
Order By: Relevance
“…The present and previous studies (Higuchi et al, 2002;Sasaki et al, 2009) have shown that the majority of the high-intensity NADH fluorescence area forms in approximately 5 min, and that PID-like waves then propagate around the high-intensity area and occasionally enlarge it. Therefore, in this study, we defined the ischemic core as the area of high-intensity NADH fluorescence that forms in 5 min and then gradually enlarges with PID-like waves, and the penumbra (potentially salvageable area) as the distal area external to the high-intensity NADH fluorescence area into which the PID-like waves propagate.…”
Section: Dynamic Changes In Nadh Fluorescencesupporting
confidence: 65%
See 2 more Smart Citations
“…The present and previous studies (Higuchi et al, 2002;Sasaki et al, 2009) have shown that the majority of the high-intensity NADH fluorescence area forms in approximately 5 min, and that PID-like waves then propagate around the high-intensity area and occasionally enlarge it. Therefore, in this study, we defined the ischemic core as the area of high-intensity NADH fluorescence that forms in 5 min and then gradually enlarges with PID-like waves, and the penumbra (potentially salvageable area) as the distal area external to the high-intensity NADH fluorescence area into which the PID-like waves propagate.…”
Section: Dynamic Changes In Nadh Fluorescencesupporting
confidence: 65%
“…The technique used for cortical NADH fluorescence imaging has previously been described in detail (Hashimoto et al, 2000;Higuchi et al, 2002;Sasaki et al, 2009). …”
Section: Technique For Cortical Nadh Fluorescence Imagingmentioning
confidence: 99%
See 1 more Smart Citation
“…Our experience with filament occlusion in rat shows that the number of flow transients clearly correlate with the histological outcome but not in a definite stepwise fashion (Luckl et al, 2009). Similarly, NADH fluorescence studies in focal ischemia showed that recurrent depolarization increases the severity of neuronal injury but only a proportion of spreading depolarizations enlarge the core (Higuchi et al, 2002; Sasaki et al, 2009). In the present study we found that the number of flow transients were significantly higher in the stimulated group.…”
Section: Discussionmentioning
confidence: 96%
“…Hypothermia (30ºC) maintained 2 h and applied before ischemia, showed that hypothermia delays the appearance, however does not modify the dynamics of propagation of peri-infarct depolarizations. The authors suggest that peri-infarct depolarizations could have a greater effect on the infarct area in hypothermic rats (Sasaki et al, 2009) and that the inefficacy to suppress peri-infarct depolarizations is the cause of the absence of hypothermia protection in several models of cerebral ischemia.…”
Section: Glutamate Release and Peri-infarct Depolarizationsmentioning
confidence: 99%